Data and Knowledge for Medical Decision Support - Blobel, Bernd (IOS Press, 2014)
Ensuring patient safety and providing high-quality health services are the dominant challenges faced by healthcare systems around the world today. The sharing of advanced knowledge and best practice in diagnosis, therapy, process optimization and prevention are essential to achieve this goal; this includes enhanced networking socially and technologically as well as the inclusion of public health and social sciences.